2023
DOI: 10.1097/pgp.0000000000000951
|View full text |Cite
|
Sign up to set email alerts
|

Uterine MEIS1::NCOA2 Fusion Sarcoma With Lung Metastasis: A Case Report and Review of the Literature

Abstract: NCOA1/2 fusion sarcomas are a recently described novel entity arising in a variety of locations with a predilection for the genitourinary tract and gynecologic organs. Despite multiple locoregional recurrences, these tumors are thought to behave in a low-grade malignant manner. Here we report a uterine MEIS1::NCOA2 fusion sarcoma with lung metastasis. The patient was a 47-yr-old woman with a history of abnormal uterine bleeding who was found to have a myometrial mass confirmed by pathology to be uterine sarcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…These genes were not only highly upregulated by VGLL1 at the mRNA level but were also identified in the ChIP-seq analysis, indicating that VGLL1-TF complexes can interact with them directly. Interestingly, several studies have shown these genes to have roles in cancer cell proliferation, invasion, angiogenesis, and EMT transition (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Taken together, our findings provide additional mechanistic evidence that VGLL1 plays an important role in modulating the expression of specific genes involved in driving tumor progression.…”
Section: Vgll1 Expression Regulates Transcription Of Genes Involved I...supporting
confidence: 58%
“…These genes were not only highly upregulated by VGLL1 at the mRNA level but were also identified in the ChIP-seq analysis, indicating that VGLL1-TF complexes can interact with them directly. Interestingly, several studies have shown these genes to have roles in cancer cell proliferation, invasion, angiogenesis, and EMT transition (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Taken together, our findings provide additional mechanistic evidence that VGLL1 plays an important role in modulating the expression of specific genes involved in driving tumor progression.…”
Section: Vgll1 Expression Regulates Transcription Of Genes Involved I...supporting
confidence: 58%
“…These genes were not only highly upregulated by VGLL1 at the mRNA level but were also identified in the ChIP-seq analysis, indicating that VGLL1-TF complexes can interact with them directly. Interestingly, several studies have shown these genes to have roles in cancer cell proliferation, invasion, angiogenesis, and EMT transition ( 26 38 ). Taken together, our findings provide additional mechanistic evidence that VGLL1 plays an important role in modulating the expression of specific genes involved in driving tumor progression.…”
Section: Resultsmentioning
confidence: 99%
“…1 Gene fusions involving NCOA2 with other fusion partners have been documented across various tumour types. These encompass acute myeloid leukaemia, 2 a small subset of colorectal carcinomas, 3 a single instance of myoepithelial carcinoma originating from the parotid gland, 4 an ependymoma-like tumour, 5 and a broadening array of distinct mesenchymal neoplasms, including mesenchymal chondrosarcoma, 6 soft-tissue angiofibroma, 7 PRRX:: NCOA1/2 rearranged fibroblastic neoplasm, 8 intraosseous spindle cell rhabdomyosarcoma, 9 congenital/infantile spindle cell rhabdomyosarcoma, 10 biphenotypic sinonasal sarcoma, 11 MEIS1::NCOA2/1 spindle cell sarcoma of the kidney, 12 uterine sarcoma with MEIS1:: NCOA2 fusion, 13 and uterine tumour resembling ovarian sex cord tumour. 14 Furthermore, singular cases of CRTC1::NCOA2 rearranged aggressive myxoid mesenchymal neoplasm involving the prostate, 15 two instances of MEF2D::NCOA2 rearranged smooth muscle tumours of the vulva, 16 as well as an NR1D1::NCOA2 rearranged soft-tissue tumour, 17 and an SRF::NCOA2 rearranged perivascular tumour of the philtrum, 18 have been reported.…”
mentioning
confidence: 99%